Tolerance to Non-Opioid Analgesics is Opioid Sensitive in the Nucleus Raphe Magnus - Tsagareli, Merab G.; Nozadze, Ivliane; Tsiklauri, Nana; Gurtskaia, Gulnaz (Frontiers in Neuroscience, 2011)
Repeated injection of opioid analgesics can lead to a progressive loss of its effect. This phenomenon is known as tolerance. Several lines of investigations have shown that systemic, intraperitoneal administration or the microinjection of non-opioid analgesics, non-steroidal anti-inflammatory drugs (NSAIDs) in the midbrain periaqueductal gray matter induces antinociception with some effects of tolerance. Our recent study has revealed that microinjection of three drugs analgin, ketorolac and xefocam into the central nucleus of amygdala produce tolerance to them and cross-tolerance to morphine. Here we report that repeated administrations of these NSAIDs into the nucleus raphe magnus (NRM) in the following four days result in progressively less antinociception, i.e. produce the development of tolerance to these drugs in mail rats. Special control experiments showed that post-treatment with μ-opioid antagonist naloxone in NRM significantly decreased antinociceptive effects of NSAIDs at the first day in behavioral tail flick reflex (TF) and hot plate (HP) latencies. At the second day, naloxone generally had trend effects in both TF and HP tests impeded the development of tolerance to the antinociceptive effect of non-opioid analgesics. These findings strongly support the suggestion on endogenous opioid involvement in NSAIDs antinociception and tolerance in the descending pain control system. Moreover, repeated injections of NSAIDs progressively lead to tolerance to them, cross-tolerance to morphine and the risk of a withdrawal syndrome. Therefore, these results are important for human medicine too.